Alqur’an Reading Skill of the Santri: A Case Study at Alqur’an Education Center of As-Syifa Central Lampung - kharis fadillah; Feri Anwar; Iis Wulandari; Nur aini; Dedi Setiawan (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2020)
Abstract To be able to absorb the essence of the message contained in the Qur'an, the first step is to read and understand the content and for that reason everyone should read and understand the Qur'an well, in depth and detail. Therefore very rational that the Qur'an receives a large portion for educational purposes for Muslims in Indonesia. It is learned in formal and non-formal education. The research was conducted to see the ability of the santri in reading Alqur’an. To conduct the research, the researcher used case study. It was conducted at Alqur’an Education Center (TPA) of As-Syifa in Central Lampung. Finally, it was found that the reading ability of the santri is still poor. There were 36 santri and there were only 20 or 56% who did not read the Quran well while only 16 or 44% read fluently